Improving the Students’ Speaking Ability by Using Suggestopedia Method at the Eighth Grade of SMP Negeri 1 Mandrehe in 2022/2023 - Dawolo, Ardianus; Maru’ao, Nursayani; Harefa, Hasrat Sozanolo; Zebua, Okniel (Journal Of Education And Teaching Learning (JETL), 2023)
Speaking ability is one of the ability to produce language in English learning. There are some problems that students faced when speaking, namely: lack of vocabulary, difficulty in conveying their ideas, rarely to speak, incorrect pronunciation, and the strategy that used by the teacher that monotous and bored. These problems could solve by using suggestopedia method. This research aimed to improve the students’ speaking ability by using suggestopedia method at the eighth grade of SMP Negeri 1 Mandrehe in 2022/2023. The researcher conducted this research by using Classroom Action Research (CAR). Instrument of the research were observation sheets, field notes and oral test. In Cycle I, the average percentage of the researcher's completed activities was 80% (good), and the percentage of the students' completed activities was 64,50% (enough). In this cycle, the students could not achieve the Minimum Competence Criterion (MCC) of 70, students' average score was 54 (less). All the students scored ? 70, with the highest score was 80 and the lowest score was 30. Furthermore, in Cycle II, the average percentage of the researcher's completed activities was 96% (excellent), and the students' completed activities was 89,50% (excellent). In this cycle, the students had achieved the Minimum Competence Criterion (MCC) of 70, the students' average score was 79 (good). None of the students scored ? 70, with the highest score was 90 and the lowest score was 65. Based on the results of this research, the researcher concluded that Suggestopedia Method could improve the students' speaking ability at the eighth grade of SMP Negeri 1 Mandrehe in 2022/2023.